Immuno-imaging of ICAM-1 in tumours by SPECT - Mosley, M; Torres, JB; Allen, D; Cornelissen, B (Elsevier, 2020)
Purpose Molecular imaging of cancer cells' reaction to radiation damage can provide a non-invasive measure of tumour response to treatment. The cell surface glycoprotein ICAM-1 (CD54) was identified as a potential radiation response marker. SPECT imaging using an 111In-radiolabelled anti-ICAM-1 antibody was explored.